2023
DOI: 10.1002/brb3.2921
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐221 rescues the loss of dopaminergic neurons in a mouse model of Parkinson's disease

Abstract: Background: Parkinson's disease (PD) is one of the most common systemic neurodegenerative diseases and is related to the loss of dopaminergic neurons in the substantia nigra. Several studies verified that microRNA (miRNAs) targeting the Bim/Bax/caspase-3 signaling axis is involved in the apoptosis of dopaminergic neurons in substantia nigra. In this study, we aimed to explore the role of miR-221 in PD. Methods: To examine the function of miR-221 in vivo, we used a well-established 6-OHDA-induced PD mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In this regard, a piece of evidence reported that miRNAs are involved in the regulation of DA-ergic circuits, α-Syn production and animal behavior. For instance, in the PD animal model 6-OHDA, the overexpression of miR-221 -usually downregulated in patients, improved motor behavior targeting the Bim/Bax/caspase-3 signaling axis, known to be involved in the apoptosis of DA-ergic cells in SN (Yao et al, 2023). In the same PD model, the overexpression of miR-375 reduces DAergic damage, oxidative stress and inflammation, by the inhibition of transcription factor specificity protein 1 (Cai et al, 2020).…”
Section: Ncrna As Biomarkers and Therapeutic Target In Pdmentioning
confidence: 99%
“…In this regard, a piece of evidence reported that miRNAs are involved in the regulation of DA-ergic circuits, α-Syn production and animal behavior. For instance, in the PD animal model 6-OHDA, the overexpression of miR-221 -usually downregulated in patients, improved motor behavior targeting the Bim/Bax/caspase-3 signaling axis, known to be involved in the apoptosis of DA-ergic cells in SN (Yao et al, 2023). In the same PD model, the overexpression of miR-375 reduces DAergic damage, oxidative stress and inflammation, by the inhibition of transcription factor specificity protein 1 (Cai et al, 2020).…”
Section: Ncrna As Biomarkers and Therapeutic Target In Pdmentioning
confidence: 99%
“…In PD, the expression of Bim is controlled by the activation of the JNK/c‐jun signalling pathway and the decrease in its translocation to the mitochondrial field (Hu et al, 2019). Based on Yao et al (2023) study, there was a notable decrease in miR‐221 levels in the blood of PD patients and brain tissue of mice with a chemically induced form of the disease. The study showed that introducing additional miR‐221 prevented the death of dopamine‐producing neurons in the mice and also influenced the Bax/caspase‐3 pathway by interacting with Bim.…”
Section: The Neuroprotective Role Of Mir‐221 In Pd: Insights From In ...mentioning
confidence: 99%